Thermal Design and Experimental Research on High-power IGBT Module Heatsink Applied in Rail Vehicle - WANG Xiong; MA Bo-le; CHEN Ming-yi; XIN Li (机车电传动)
Thermal resistance of heatsink was calculated with heat transfer empirical formulas and simulated with Icepak software, for testing accuracy of which, experiments of thermal resistances were carried out. Comparison of the results proved that Icepak simulation could meet engineering applying requirement, as well as modified empirical formulas method.